Amerikanische entomologische Dissertationen, 1962 - 1965. - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1968)
As second part there are recorded entomological dissertations accepted by universities of the U.S.A. between 1962 and 1965. The titles were taken from the "Dissertation Abstracts" (University Microfilms, Inc., Ann Arbor).